Determinan Penggunaan E-Money pada Mahasiswa Program Studi Akuntansi - Pangestu Miftahul Wahid Azis; Sulistyowati Erna (Economic Reviews Journal, 2024)
This article discusses the use of QRIS e-money among accounting study program students at the National Development University "Veteran" East Java if the use of e-money is not balanced with a good perception of security and financial awareness. Regarding the use of e-money, this research is important to conduct in order to provide a clear picture of the influence of security perceptions, consumer behaviour and financial literacy. This research uses the Partial Least Square (PLS) method with the help of SmartPLS. The results of the research show: 1. Perception of security has a significant positive effect on the use of e-money among students in the Accounting study program at the National Development University "Veteran" East Java. 2. Consumptive behaviour has a significant positive effect on the use of e-money among students in the Accounting study program at the National Development University "Veteran" East Java. 3. Financial literacy has a significant positive effect on the use of e- money among students in the Accounting study program at the National Development University "Veteran" East Java. Artikel ini membahas tentang penggunaan e-money QRIS pada mahasiswa program studi akuntansi Universitas Pembangunan Nasional “Veteran” Jawa Timur jika penggunaan e-money tidak diimbangi dengan persepsi keamanan dan kesadaran finansial yang baik. Terkait penggunaan e-money penelitian ini penting untuk dilakukan agar dapat memberikan gambaran yang jelas tentang pengaruh persepsi keamanan, perilaku konsumtif, dan literasi keuangan. Penelitian ini menggunakan metode Partial Least Square (PLS) dengan bantuan SMartPLS. Hasil penelitian menunjukkan: 1.Persepsi keamanan berpengaruh positif signifikan terhadap penggunaan e-money pada mahasiswa program studi Akuntansi Universitas Pembangunan Nasional “Veteran” Jawa Timur. 2. Perilaku konsumtif berpengaruh positif signifikan terhadap penggunaan e-money pada mahasiswa program studi Akuntansi Universitas Pembangunan Nasional “Veteran” Jawa Timur. 3. Literasi keuangan berpengaruh positif signifikan terhadap penggunaan e-money pada mahasiswa program studi Akuntansi Universitas Pembangunan Nasional “Veteran” Jawa Timur.